2014
DOI: 10.4137/ebo.s14713
|View full text |Cite
|
Sign up to set email alerts
|

Similarity/Dissimilarity Analysis of Protein Sequences Based on a New Spectrum-Like Graphical Representation

Abstract: Sequence comparison is one of the foundations in bioinformatics, which can be used to study evolutionary relations among the sequences. In this study, a 2D spectrum-like graphical representation of protein sequences is presented based on the hydrophobicity scale of amino acids. The frequencies of amplitudes of 4-subsequences are adopted to characterize a spectrum-like graph, and a 17D vector is used as the descriptor of protein sequence. The χ2 value of compatibility test is performed. New similarity analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 38 publications
0
9
1
Order By: Relevance
“…This is one of the most used and reliable tools on searching for sequence similarity and identity. Sequence similarity comparison, such as for DNA, RNA, and protein, is the base of bioinformatics, and this kind of analysis improve the protein function prediction, being one of the most important analysis in HPs characterization (Pearson, 2013;Yao et al, 2014).…”
Section: Search For Patterns Of Similarity With Other Proteinsmentioning
confidence: 99%
“…This is one of the most used and reliable tools on searching for sequence similarity and identity. Sequence similarity comparison, such as for DNA, RNA, and protein, is the base of bioinformatics, and this kind of analysis improve the protein function prediction, being one of the most important analysis in HPs characterization (Pearson, 2013;Yao et al, 2014).…”
Section: Search For Patterns Of Similarity With Other Proteinsmentioning
confidence: 99%
“…On the other hand, ClustalW also correctly separates the proteins into their correct groups (Fig.7). Yao et al [18] Ellakani and Mahran [27] Zhang et al [15] Mu et al [28] Liu et al [29] Wu et al […”
Section: Similarity Analysis Of Coronavirus Spike Proteinsmentioning
confidence: 99%
“…Authors showed that the proposed model is easier and quicker in handling protein sequences than multiple alignment methods and gives protein classification greater evolutionary significance at the amino acid sequence level. In [18], author presented a 2D spectrumlike graphical representation of protein sequences based on the hydrophobicity scale of amino acids. The frequencies of amplitudes of 4-subsequences were adopted to characterize a spectrum-like graph, and a 17D vector was used for numerical representation of a protein sequence.…”
Section: Introductionmentioning
confidence: 99%
“…For the widespread application of the moment of inertia in many gene numerical representation method 10 , 11 , 15 , 16 , the normalized moments of inertia for each massive sub-curve of Fermat spiral are calculated as the numerical representation of formal DNA sequence in this paper. To the convenience of calculation, the transformation of polar coordinates to plane coordinates is performed: …”
Section: Numerical Representationmentioning
confidence: 99%